Book of Papers: XIV Simpósio Nacional de Sistemas Prediais [SISPRED 2021] - Martins de Paula, Heber; Prado Abreu Reis, Ricardo (SIMPÓSIO NACIONAL DE SISTEMAS PREDIAIS, 2021)
Book of Papers: XIV Simpósio Nacional de Sistemas Prediais [SISPRED 2021]